Inactivation of the monofunctional peptidoglycan glycosyltransferase SgtB allows Staphylococcus aureus to survive in the absence of lipoteichoic acid - Karinou,E; Schuster,C; Pazos,M; Vollmer,W; Grundling,A (Journal of Bacteriology, 2018)
The cell wall of Staphylococcus aureus is composed of peptidoglycan and the anionic polymers lipoteichoic acid (LTA) and wall teichoic acid. LTA is required for growth and normal cell morphology in S. aureus. Strains lacking LTA are usually viable only when grown under osmotically stabilizing conditions or after the acquisition of compensatory mutations. LTA-negative suppressor strains with inactivating mutations in gdpP, which resulted in increased intracellular c-di-AMP levels, were described previously. Here, we sought to identify factors other than c-di-AMP that allow S. aureus to survive without LTA. LTA-negative strains able to grow in unsupplemented medium were obtained and found to contain mutations in sgtB, mazE, clpX, or vraT. The growth improvement through mutations in mazE and sgtB was confirmed by complementation analysis. We also showed that an S. aureus sgtB transposon mutant, with the monofunctional peptidoglycan glycosyltransferase SgtB inactivated, displayed a 4-fold increase in the MIC of oxacillin, suggesting that alterations in the peptidoglycan structure could help bacteria compensate for the lack of LTA. Muropeptide analysis of peptidoglycans isolated from a wild-type strain and sgtB mutant strain did not reveal any sizable alterations in the peptidoglycan structure. In contrast, the peptidoglycan isolated from an LTA-negative ltaS mutant strain showed a significant reduction in the fraction of highly cross-linked peptidoglycan, which was partially rescued in the sgtB ltaS double mutant suppressor strain. Taken together, these data point toward an important function of LTA in cell wall integrity through its necessity for proper peptidoglycan assembly.